2017
DOI: 10.1016/j.semcdb.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Chasing the recipe for a pro-regenerative immune system

Abstract: Identification of the key ingredients and essential processes required to achieve perfect tissue regeneration in humans has so far remained elusive. Injury in vertebrates induces an obligatory wound response that will precede or overlap any regeneration specific program or scarring outcome. This process shapes the cellular and molecular landscape of the tissue, influencing the success of endogenous repair pathways or for potential clinical intervention. The involvement of immune cells is also required for aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
79
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 97 publications
0
79
0
1
Order By: Relevance
“…During traumatic injury the inflammatory response must navigate a fine balance between the initial protection against infection versus the eventual promotion of a functional repair response (Godwin et al, 2016). In classical epimorphic regeneration models, such as the salamander limb or the zebrafish fin, recent macrophage depletion studies provide clear evidence that this balance is tipped toward the promotion of a functional regeneration response (Godwin et al, 2013;Petrie et al, 2014), and our study adds the mouse digit tip to this list of macrophage-dependent regenerative responses.…”
Section: Macrophages Play Multiple Roles In Epimorphic Regenerationmentioning
confidence: 76%
“…During traumatic injury the inflammatory response must navigate a fine balance between the initial protection against infection versus the eventual promotion of a functional repair response (Godwin et al, 2016). In classical epimorphic regeneration models, such as the salamander limb or the zebrafish fin, recent macrophage depletion studies provide clear evidence that this balance is tipped toward the promotion of a functional regeneration response (Godwin et al, 2013;Petrie et al, 2014), and our study adds the mouse digit tip to this list of macrophage-dependent regenerative responses.…”
Section: Macrophages Play Multiple Roles In Epimorphic Regenerationmentioning
confidence: 76%
“…It is now widely accepted that KCs derive from colony-stimulating factor 1 receptor (CSF1R) + erythromyeloid progenitors in the yolk sac that migrated to the liver around embryonic day (E)10.5 in mice. (42)(43)(44) This has been demonstrated using Csf1r reporter mice and refined by a later study that showed KCs derived from hematopoietic stem cells that migrated to the liver at E10.5, using KIT proto-oncogene receptor tyrosine kinase (Kit) for fate mapping. (43,45) KCs, like other tissue-resident macrophages, self-renew at steady state independently of bone marrow progenitors at least up to 9 months of age in mouse.…”
Section: Kupffer Cellsmentioning
confidence: 96%
“…454Further studies are required to clarify the specific role that macrophages play in osteogenesis during 455 blastema differentiation. 456During traumatic injury the inflammatory response must navigate a fine balance between the 457 initial protection against infection versus the eventual promotion of a functional repair response 458(Godwin et al, 2016). In classical epimorphic regeneration models, such as the salamander limb or the 459 zebrafish fin, recent macrophage depletion studies provide clear evidence that this balance is tipped 460 toward the promotion of a functional regeneration response(Godwin et al., 2013; Petrie et al, 2014), 461 and our study adds the mouse digit tip to this list of macrophage-dependent regenerative responses.…”
mentioning
confidence: 99%